Advanced Imaging for Congenital Left Ventricular Diverticulum in a Dog: The Role of Electrocardiosynchronous CT - Miki Hirose; Lina Hamabe; Kazumi Shimada; Aki Takeuchi; Kazuyuki Terai; Aimi Yokoi; Ahmed Farag; Akari Hatanaka; Rio Hayashi; Katsuhiro Matsuura; Ryou Tanaka (Animals)
A 2-month-old Shiba Inu was presented to an emergency veterinary clinic with decreased activity and was diagnosed with pulmonary hypertension secondary to a ventricular septal defect. The dog was referred to the TUAT Veterinary Medical Center for further evaluation. During treatment, a diverticulum was incidentally identified at the apex of the left ventricle. While the diverticulum caused no clinical symptoms, a cardiac synchronous computed tomography (CT) scan was performed to accurately assess its anatomical location and size. This case highlights the value of advanced imaging techniques in diagnosing complex congenital cardiac anomalies.